Regional Culinary Heritage Europe network as a factor of culinary tourism development – Wielkopolska Region (Greater Poland) case study (Geography and Tourism, 2017)
The main objective of the Regional Culinary Heritage Europe network is to develop regions through regional food and culinary traditions. Its objective is also to show consumers and tourists how to find local and regional food in Europe. Therefore, the initiative can be considered as an important factor for the culinary tourism development. For the purpose of this paper, the author has decided to present some network members, their functioning and local coordination activities undertaken to develop and promote the idea of the network, also in tourism, as exemplified by Wielkopolska Region (Greater Poland).The network of Regional Culinary Heritage Europe is a well-known and recognisable initiative in the food and tourismsectors, but the author of this paper has decided to investigate, using a short interview questionnaire, whether touriststravelling around Wielkopolska are also familiar with the network’s logo and objectives. Unfortunately, they are not.